Prototype design of an IoT-based dryer and temperature monitoring device and test its utilization on the dryness and proximate levels of seaweed - Rahman, Samsu Adi; Ayuba, Yusuf (Universitas Malikussaleh, 2024)
Seaweed has potential as a commodity for small and medium-scale businesses, but its quality is low due to conventional drying which experiences contamination and dries slowly. This research aims to produce a prototype IoT-based seaweed dryer to improve the quality of seaweed. The stages of this research are designing a prototype drying device, drying seaweed tests, and proximate analysis of seaweed. This research resulted in a 300W prototype using IoT components, including a solid state relay, Arduino Uno R3, potentiometer, thermocouple, 12C LCD, and SIM 800L V2 GSM GPRS module, with temperature control via an Android application. Optimal drying occurs at 60 oC, producing dried seaweed weighing 470.90 g from 1000 g. Water content decreases as temperature increases to 60 oC (18.85%), 50 oC (23.11%), 40 oC (32.30%), and conventional (34.50%). The highest protein, fat and carbohydrate content was at 60 oC, indicating drying efficiency at that temperature. Based on these results, it was concluded that using a dryer with a temperature of 60 oC was the best and most efficient.Keywords: Dryer; IoT; production; proximate; seaweed